Policy Content Analysis of Rawapening Lake Management Team - Kalmah, Kalmah; Larasati, Endang; Purnaweni, Hartuti; Kismartini, Kismartini (Technium Social Sciences Journal, 2022)
Rawapening lake is one of multifunction lake in central java province. It is one of the priority lake in Indonesia. Rawapening Lake has been degraded due to its function. The most visible impacts are the decreasing of physical and chemical quality of the lake water and the decreasing of the lake carrying capacity. There have been several policies of Lake management in Indonesia, but most of lakes condition in Indonesia are still degrading. The Governor Decision number 610 was issue in 2019. This policy is about establishment of Rawapening Lake management team form multi stakes holder which consist of steering team, implementing team which consist of five working groups. Since the establishment of Rawapening lake management team, reportedly there has been positive changes in Rawapening condition. The content of this policy can be the key to sustainable lake management in Indonesia. The content analysis of the Rawapening management team is subjected in to three focuses as follows: the duties of steering team, the duties of implementing team, what have the working group done as part of the implementing team.